Excipient Interactions in Glucagon Dry Powder Inhaler Formulation for Pulmonary Delivery - Md Abdur Rashid; Amged Awad Elgied; Yahya Alhamhoom; Enoch Chan; Llew Rintoul; Ayman Allahham; Nazrul Islam (MDPI AG, 2019)
Purpose: This study describes the development and characterization of glucagon dry powder inhaler (DPI) formulation for pulmonary delivery. Lactose monohydrate, as a carrier, and L-leucine and magnesium stearate (MgSt) were used as dispersibility enhancers for this formulation. Methods: Using Fourier-transform infrared (FTIR) spectroscopy, Differential Scanning Calorimetry (DSC), and Raman confocal microscopy, the interactions between glucagon and all excipients were characterized. The fine particle fractions (FPFs) of glucagon in different formulations were determined by a twin stage impinger (TSI) using a 2.5% glucagon mixture, and the glucagon concentration was measured by a validated LC-MS/MS method. Results: The FPF of the glucagon was 6.4%, which increased six-fold from the formulations with excipients. The highest FPF (36%) was observed for the formulation containing MgSt and large carrier lactose. The FTIR, Raman, and DSC data showed remarkable physical interactions of glucagon with leucine and a minor interaction with lactose; however, there were no interactions with MgSt alone or mixed with lactose. Conclusion: Due to the interaction between L-leucine and glucagon, leucine was not a suitable excipient for glucagon formulation. In contrast, the use of lactose and MgSt could be considered to prepare an efficient DPI formulation for the pulmonary delivery of glucagon.